Political vocabularies: FDR, the clergy letters, and the elements of political argument - Stuckey, Mary E. (Rhetoric and public affairs series, 2018)
Introduction: answering the call : creating political vocabularies -- By benefit of clergy : authoritative political vocabularies -- Witnessing politics : the depictive element of political vocabularies -- Revelations : naturalizing political vocabularies -- The American Eden : mythic elements of political vocabularies -- Making a city on a hill : political vocabularies and national policy -- Conclusion : creating a democratic ecclesia through shared political vocabularies.